PENGEMBANGAN SISTEM MONITORING ALIRAN DAN KUALITAS AIR SUNGAI MENGGUNAKAN PELAMPUNG BERBASIS SMART ENVIRONMENT - Nasution, Subhan Fahmi; Harmadi, Harmadi; Suryadi, Suryadi; Widiyatmoko, Bambang (Jurusan Fisika FMIPA Universitas Andalas, 2024)
Efficient and accurate river water quality monitoring is needed to support laboratory testing based on on-site sampling. Therefore, we have developed a monitoring system for river flow and water quality using sensor-equipped buoys and the Internet of Things (IoT) concept. An ESP32 NodeMCU microcontroller integrated with WiFi and compatible with Arduino IDE is used in the system. The buoy is equipped with GPS to determine the position and flow speed and sensors to measure water quality parameters of pH and temperature. Data on position, flow velocity, and water quality parameters are transmitted over a WiFi network using the MQTT protocol. The data is recorded by the buoy and uploaded and displayed on the adafruit.io platform. Positioning was done by comparing the values displayed on the Neo-6M GPS with the Maps application on the smartphone. The results show that the GPS coordinate values are accurate. The water quality parameter values obtained have an error rate of 3.3% for the pH sensor and 1.02% for the temperature sensor. Thus, the system we have developed has the potential to be used as a substitute for field sampling-based river water quality monitoring systems.